Organizatoriskās transformācijas strukturēšana tehnoloģiju uzņēmumā - Lizama Muga, Julián Carlos (Latvijas Universitāte, 2024)
The purpose of this Thesis is to understand how an Organizational Transformation can help a company increase its chances of survival, which are the pillars to focus on, what are the best practices, key success factors and challenges; and from there to provide a structure for an Organizational Transformation in a technology company. The study was developed in a small 10 year old technology company, where it explored understanding its operation over the years and future objectives. After a review of the literature, it was determined that there are four pillars that must be considered in an Organizational Transformation: Culture, Process, Strategy and Structure. Furthermore, communication, resistance management, commitment of those involved and alignment of the four pillars are essential for success. A qualitative approach was chosen, where semi-structured interviews were conducted, composed of 16 questions. The answers were categorized using Atlas.ti software, and assigned to one of the four established pillars. The analysis indicated that the company was informal, lacked defined processes, had communication problems, unclear strategy and scarce alignment of the pillars. Based on this, a Transformational Roadmap with concrete actions was generated, which should be in charge of a Transformational Leader, and can serve as a reference for future studies.
Structuring the organizational transformation of a technology company
Keywords: Ekonomika un uzņēmējdarbība; Organizational Transformation; Culture; Process; Strategic; Structure